Argumented Reality dalam Komunikasi Pemasaran melalui Perangkat Mobile - ., Diah Virgin; ., Irwansyah (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The use of technology not only enhances people's desire to purchase products but also serves as a communication tool that aids customers in fulfilling their needs. One highly beneficial digital technology for marketing is Augmented Reality (AR). AR elevates competitive advantages. However, there are several challenges impeding the adoption of AR technology. Therefore, it is crucial to identify both the difficulties and opportunities in marketing that leverage AR. The objective of this research is to provide an overview of the various challenges and opportunities presented by AR technology to garner attention in marketing communication and to evaluate the future prospects of this technology. A systematic qualitative literature review was conducted on eight publications from 2018 to 2020. This study identified two challenges and four prospects for AR technology in this context.